The balance of patient and learners needs in non-profit, public and for-profit teaching hospitals: An analysis of average patient satisfaction ratings of hospitals on a German hospital rating platform. (2nd July 2020) - Liberatore, Florian; Angerer, Alfred; Kriech, Sarah
ABSTRACT: Background: Teaching hospitals have to balance patient and learner needs in their daily routines. To respond to these challenges, non-profit hospitals may perform differently than public and for-profit hospitals because of their non-distribution constraint. Purposes: This study analyzes patient satisfaction data of non-profit teaching hospitals in comparison to teaching hospitals with for-profit and public ownership status. Patient satisfaction is assumed to be an indicator of how patient needs are met regardless of the teaching goals. Approach: The average patient satisfaction ratings for German hospitals ( n = 1461) that were published on the 'klinikbewertungen.de' German hospital rating platform were collected for a cross-section analysis. Findings: The data show that non-profit teaching hospitals are better rated than for-profit and public teaching hospitals. Non-profit hospitals seem to be more competent in handling the balance between societies' needs for clinical training and patient needs for a favorable service experience. Practice implications: For-profits hospitals should revisit their business model once they get involved in the provision of public values such as education.